THE IMPLEMENTATION OF 7E LEARNING CYCLE IN SUB MATERIAL NEWTON LAWS OF MOTION TO TRAIN STUDENTS SCIENCE PROCESS SKILLS - ALWANUN ZAIM, MOCHAMAD; , SUPARDIYONO (Inovasi Pendidikan Fisika, 2019)
This research reported the implementation of learning cycle 7E to train science process skills and describing the student?s science process skills. The research was pre experimental with one group pretest posttest design. The teaching learning materials were validated before being used. The research data were analyzed by implementation learning analysis, pre-test and post-test analysis, worksheet assessment analysis. The change of students science process skills were analyzed by t-paired test. The results of the research showed that: (1) the quality of learning cycle 7E implementation gots very good category. (2) Students science process skills got a significant improvement based on the paired t-test. Keywords: Learning Cycle 7E, Newton Laws, Science Process Skills.